Hardware design of IoT-based water quality control system for Vannamei post-larvae shrimp - Satria, Anas; Novandi, Arief Ilham; Kusuma, Purba Daru; Septiawan, Reza Rendian (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2024)
The vannamei shrimp is a type of shrimp that has a natural habitat in the Pacific Coast, and Mexico. This shrimp entered Indonesia in 1996 when tiger shrimp experienced a decline in production due to disease attacks caused by the White Spot virus. Demand for this shrimp immediately increased rapidly, requiring innovation to keep shrimp yields in line with market demand. The problem in vaname shrimp farming is water quality, especially water temperature conditions where shrimp live. This shrimp prefer water conditions that have temperatures around 27-29°C. A water quality control system was developed to maintain water conditions in accordance with the best conditions for P. vannamei shrimp to increase yields due to reduced mortality rates. The result is the system can help increase the survival of the shrimp.